2018
DOI: 10.1161/circresaha.117.311648
|View full text |Cite
|
Sign up to set email alerts
|

S1P–S1PR2 Axis Mediates Homing of Muse Cells Into Damaged Heart for Long-Lasting Tissue Repair and Functional Recovery After Acute Myocardial Infarction

Abstract: Muse cells may provide reparative effects and robust functional recovery and may, thus, provide a novel strategy for the treatment of acute myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
191
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(217 citation statements)
references
References 39 publications
5
191
0
Order By: Relevance
“…Because bone marrow‐derived mesenchymal stromal cells (MSCs) were confirmed to possess significant self‐renewability, low immunogenicity, and ability to differentiate into a variety of specialized cells (Oreffo, Cooper, Mason, & Clements, ; Pittenger et al, ), it has been wildly applied to cell‐based strategies for tissue engineering and regenerative medicine such as treatment of ischemia‐reperfusion injury and heart diseases (Lo et al, ; Yamada et al, ). Studies have reported that transplantation of MSCs could lead to improved neovascularization of ischemic myocardium, inhibition of myocardial fibrosis, and restoration of myocardial contractile function (Epstein, Luger, & Lipinski, ; Yan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Because bone marrow‐derived mesenchymal stromal cells (MSCs) were confirmed to possess significant self‐renewability, low immunogenicity, and ability to differentiate into a variety of specialized cells (Oreffo, Cooper, Mason, & Clements, ; Pittenger et al, ), it has been wildly applied to cell‐based strategies for tissue engineering and regenerative medicine such as treatment of ischemia‐reperfusion injury and heart diseases (Lo et al, ; Yamada et al, ). Studies have reported that transplantation of MSCs could lead to improved neovascularization of ischemic myocardium, inhibition of myocardial fibrosis, and restoration of myocardial contractile function (Epstein, Luger, & Lipinski, ; Yan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, if the S1PR2 gene was knocked out in Muse cells, they would lose the homing feature. These results suggest that the S1P-S1PR2 axis is the mechanism for Muse cell homing to lesion areas [22].…”
Section: Characteristics Of Muse Cellsmentioning
confidence: 72%
“…Gene analysis showed that CDH1 was overexpressed and alpha-6 integrin (ITGA6) and Lin28 were down-regulated in Muse cells [4,6,20,21]. Animal studies in the testis of severe combined immunodeficient mice (SCID) and myocardial infarction sites of rabbits demonstrated that injected Muse cells did not form tumors 6 months post-injection [1,4,22]. Moreover, Muse cells are a subpopulation of MSCs, which have been safely transplanted in basic and clinical studies [23,24].…”
Section: Characteristics Of Muse Cellsmentioning
confidence: 99%
See 2 more Smart Citations